Implementasi Algoritma Haversine Formula dan Location Based Service Pada Aplikasi Pencarian Lokasi Bird Contest Berbasis Android - Prihantoro, Dimas Dwi; Wahyuddin, Mohammad Iwan (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
At this time, the chirping bird competition has become so popular that it can be said to be a trend in Cibinong District. The number of enthusiastic chirping maniacs who have just entered this competition, not a few of the chirping maniacs do not know where the competition is taking place in Cibinong District. With the lack of information about the competition venue in Cibinong District. So a location search application was made using the Location Based Service method as the location of the user's point and the Haversine Formula Algorithm as a measure of the distance. From the measurement results of the haversine formula by comparing the application's haversine distance to the distance of google maps to get an average value of 0.039 kilometers.